D4N2024 Presentation Showcase – Plenary Session: Approaches to connecting the dots around food systems and nutrition: Evidence to policy and action - Swaminathan, Soumya; Pandey, Pooja; Talukder, Md Ruhul Amin; Das, Jai K. (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – Plenary Session: Approaches to connecting the dots around food systems and nutrition: Evidence to policy and action